PERBANDINGAN METODE HAZARD MULTIPLIKATIF DAN ADITIF PADA LAJU PERBAIKAN KONDISI KLINIS PASIEN STROKE DI RS MH THAMRIN CILEUNGSI TAHUN 2021 - Zulfa Luthfiyyah Ayunda; Triastuti Wuryandari; Suparti Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2025)
Stroke is a condition that can result in permanent brain damage or even death. In Indonesia, the prevalence of stroke increased from 7% in 2013 to 10.9% in 2018. Numerous factors can affect a stroke patient's ability to recover. Survival analysis is a method that can be used to identify the variables that influence stroke patient’s ability to recover. Cox proportional hazard and Lin-ying additive hazard approaches were utilized in this study to analyze stroke patient data from MH Thamrin Cileungsi Hospital. The most widely used regression model for survival data is the Cox proportional hazard which makes the assumption that the ratio between the hazard functions of various people is constant. In contrast, in additive hazard regression there is no assumption of proportionality. Age and cardiac history are the factors that have an impact on how well stroke patients recover, according to the findings. The Lin-Ying additive hazard approach yields the best results since its RMSE value is lower (0.3808777) than that of the cox proportional hazard model (0.9248512).